Dual-curvature cavity for improved p-type FinFET performance. (13th July 2018) - Peng, Jianwei; Lo, Hsien-Ching; Zhao, Pei; He, Xiaoli; Hu, Yue; Shi, Yongjun; Qi, Yi; Vinslava, Alina; Shen, Yanping; Hong, Wei; Choi, Dongil; Adams, Charlotte; et al.
Abstract: This work presents a new dual-curvature cavity that enables p-type transistor electrical I on – I off performance improvement in FinFET technology. A dual-curvature cavity is a conventional ball-shaped cavity with an additional smaller cavity at the bottom formed through further pushing down the Fin and spacers in the gate canyon. This new cavity design benefits on-state current ( I on ) through enabling larger SiGe source/drain with deeper cavity while it minimizes the penalty of drain leakage ( I off ) increase though keeping the additional cavity away from the channel. In this work, devices with dual-curvature cavity demonstrated 3%–6% I on – I off performance improvement for different threshold voltage flavors in a mature 14 nm production line.